A study on normal reference values of the left ventricular strain parameters in young adults - Das, Malyaban; Kuila, Madhumita; Swapan Kumar Halder (Asian Journal of Medical Sciences, 2024)
Background: The left ventricular (LV) function is an important prognostic determinant of cardiopulmonary pathologies in adult. Clinical application of cardiac strain by two-dimensional speckle tracking echocardiography to measure LV function requires knowledge of the range of normal values. Reference values and associated variations of the deformation measures need to be “firmly established before routine clinical adoption” of LV strain measurements can be implemented in Indian population. Aims and Objectives: This study aims to establish normal values of LV strain parameters in normal Indian population. Materials and Methods: An observational, cross-sectional, single-center, hospital-based study. The study period October 2021–October 2022 in Nil Ratan Sircir Medical College, Kolkata. Cardiologically healthy adult subjects (sample size 250) both male and female, aged 18–45 years who were healthcare professionals of this medical college and hospital were included in the study. Routine history taking and investigations were done. Echodoppler was done with special emphasis on LV strain parameters. Results: Distribution of mean LV circumferential strain (LVCS) with age in years was statistically not significant (P=0.8068). The mean value in male and female were −18.9574(±0.9049) and −19.0257(±0.8908) respectively. In the current study, LVCS did not vary in statistically significant a way among different age groups too. The mean values in male and female were −22.5887(±1.8065) and −22.3312(±1.9007) respectively. Conclusion: This current study failed to show significant differences in LV strain parameters between age groups or male and female in Eastern India Population.